Attitudes Among Male and Female University Professors, and other Categories of University Employees, to Working up to and Beyond Normal retirement age - Kadefors, Roland; Schaller, Joseph; Thång, Per-Olof; Pestat, Elin (Nordic Journal of Working Life Studies, 2016)
A study was undertaken in order to identify variables predicting the willingness of male and female university professors, and other employment categories, to work up to and beyond normal retirement age (65 years). Employees were asked by means of a questionnaire about their willingness to continue working to age 67, or to age 70, if they were given the chance. Hierarchical multiple regression analysis was carried out (N = 3,019; 59.8% women and 40.2% men). The interest to continue working into old age was significantly higher in men than in women (p<0.01). Among independent variables, age, position, and work satisfaction predicted women’s as well as men’s interest to work to age 67 and 70, whereas among women perceived health predicted the willingness to work to age 67. Professors and lecturers were the categories showing the highest interest to work to age 70, compared to administrative and technical personnel; men showed significantly higher interest than women among lecturers and administrative personnel. The study emphasizes the effects of position and gender on willingness to continue working into old age, but identifies in addition also work satisfaction and age as significant predictors.